2000
DOI: 10.1128/iai.68.7.4200-4206.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathogenic Effect of Trichomonas vaginalis on Human Vaginal Epithelial Cells Cultured In Vitro

Abstract: In this study we established human vaginal epithelial cells (hVECs) in culture and evaluated their interaction with Trichomonas vaginalis parasites to complement previous studies using other cell types. Primary cultures of hVECs were established. Contaminating fibroblasts were separated from epithelial cells by differential trypsinization. Specific antibody staining revealed that over 92% of cells in hVEC monolayers were epithelial cells. T. vaginalis adhered to hVECs and produced severe cytotoxic effects resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 33 publications
7
83
2
Order By: Relevance
“…Previous in vitro studies have addressed the interaction of T. vaginalis with human fibroblasts (Alderete & Garza 1985, Gilbert et al 2000. The authors of these studies concluded that the parasites were able to attach to the cells, but did not induce cytotoxicity (Alderete & Garza 1985, Gilbert et al 2000.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous in vitro studies have addressed the interaction of T. vaginalis with human fibroblasts (Alderete & Garza 1985, Gilbert et al 2000. The authors of these studies concluded that the parasites were able to attach to the cells, but did not induce cytotoxicity (Alderete & Garza 1985, Gilbert et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of these studies concluded that the parasites were able to attach to the cells, but did not induce cytotoxicity (Alderete & Garza 1985, Gilbert et al 2000. In addition, recent work in which mice were used as a host model for T. vaginalis infection demonstrated that trichomonas causes alterations in the connective tissue (Escario et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichomonas vaginalis, a protozoan parasite, is the causative agent of trichomoniasis, the most common nonviral sexually transmitted disease in humans [1]. This parasite has a worldwide distribution and it infects 250 to 350 million people worldwide [2].…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory mice, Tritrichomonas foetus maintains its shape and flagella and adheres to and injure vaginal and endometrial epithelial cells (Singh et al 2004;Gilbert et al 2000;Midlej et al 2009;Vilela and Benchimol 2011;Pereira-Neves et al 2012). Inhibition of cell division and endometrial inflammation were detected in vitro in oviduct organ culture models (Benchimol et al 2006;Ma et al 2011) .…”
Section: Pathogenesismentioning
confidence: 99%